2006
DOI: 10.1007/s11242-005-1125-7
|View full text |Cite
|
Sign up to set email alerts
|

Water Absorption into Construction Materials: Comparison of Neutron Radiography Data with Network Absorption Models

Abstract: Two different porous building materials have been previously measured and analysed (El-Abd and Milczarek, 2004, IEEE Trans. Nuclear Sci.; El-Abd et al., 2004, J. Phys. D) using neutron radiography to measure the water front position over time. The results from this experimental approach show a similar behaviour to the predictions from idealised model structures, in that there is a cross over point where the fastest rate of absorption at first favours the finer structure material and at later times favours th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…This results in a preferred pathway absorption through a network of pores defined by the inertial and plug-like flow within the fine scale connectivity. This has been demonstrated by the work of Schoelkopf et al and Gane and Ridgway using real and corresponding model network structures (Schoelkopf et al 2000a(Schoelkopf et al , 2004aGane 2004;Ridgway et al 2006a). The study reported here, sets out to define the saturation level as a function of distance approaching the wetting front so as to quantify the spatial definition of the preferred pathway mechanism as a function of reducing structural permeability (binder level and depth/time).…”
Section: Liquid Uptake Into Coating Structuresmentioning
confidence: 83%
“…This results in a preferred pathway absorption through a network of pores defined by the inertial and plug-like flow within the fine scale connectivity. This has been demonstrated by the work of Schoelkopf et al and Gane and Ridgway using real and corresponding model network structures (Schoelkopf et al 2000a(Schoelkopf et al , 2004aGane 2004;Ridgway et al 2006a). The study reported here, sets out to define the saturation level as a function of distance approaching the wetting front so as to quantify the spatial definition of the preferred pathway mechanism as a function of reducing structural permeability (binder level and depth/time).…”
Section: Liquid Uptake Into Coating Structuresmentioning
confidence: 83%
“…The studies were performed on a sample of fired clay brick of effective porosity ∼ 30% (36% as determined by destructive mercury intrusion), of the same kind as used previously as the medium in spontaneous imbibition studies [12][13][14]. The effective capillary radius of the sample as determined from the rate of water imbibition was ∼ 5.5 nm.…”
Section: Methodsmentioning
confidence: 99%
“…This method requires good experience and sophisticated analysis to fulfil its potential performance. 4) Radiation attenuation techniques: These include X-ray system [5], gamma ray system [6] and neutron radiography system [7][8][9][10][11][12][13][14][15]. Their attenuations can be related to water content within the materials.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Pleinert [7] studied the moisture distribution in mortar under drying condition by means of neutron radiography with high resolution; Hassanein [8,9] also presented the possibility and successfully studied the water imbibition into different building stones using neutron radiography; Masschaele [10] studied fluid motion into porous sand and limestone in three dimensions visibly; and Ridgway [11] established the network absorption model based on the experimental water absorption data of red clay brick and white siliceous brick by neutron radiography. Pugliesi [12] has utilized neutron radiography to observe cracks in concrete.…”
Section: Introductionmentioning
confidence: 99%